Innovations in agricultural marketing: a case study of e-tendering system in Karnataka, India - Pavithra S; Gracy C P; Raka Saxena; Ganesh Gowda Patil (Agricultural Economics Research Review, 2023)
This paper analyses the effectiveness and challenges of e-tendering marketing system with a focus on pigeon pea. The results indicate that e-tendering has been successful in reducing transaction time, bringing transparency in price discovery and increasing market revenue, besides enhancing market competition. The system, however, has not been effectively implemented among all the markets because of traders’ resistance. By identifying the factors behind the success of e-tendering in some markets and the lack thereof in others, we provide certain key insights into obstacles in successful implementation of innovative marketing reforms with specific reference to the e-National Agricultural Market (e-NAM).